How is the concept of organisational excellence defined in a multi-cultural society (like Singapore)? - Lau, Lay Hong (2014)
The subject of interest in this research is the applicability of the concept of organisational excellence (In Search of Excellence, by Peters & Waterman) on a multi-racial society like Singapore. The eight attributes of organisational excellence were established based on surveys done in the United States of America. Through this research, we hope to gain insight on how the local business managers view the eight attributes. From our analysis of the results, we find that the concept on organisational excellence is indeed not culture-free. The three ethnic groups in Singapore, namely the Chinese, Malays and Indians, place different emphasis on the eight criteria. It can be noted that Chinese managers emphasise more on criteria like “closeness to customer” and “productivity through people”. On the other hand, Malay managers emphasise more on “stick to the knitting” and “simultaneous loose-tight properties”. Indian counterparts, in contrast, are found to be placing more emphasis on “productivity through people”. We applied Hofstede's dimensions of cultural differences in interpreting our findings. In terms of culture differences, Malay culture is geared towards values like “power distance”, “uncertainty avoidance” and “collectivism”. Indian counterparts, on the other hand, are more masculine than the other two ethnic groups. Based on our findings, three recommendations are made. It is recommended that all managers should be aware of cultural differences of the various ethnic groups. With an understanding of the cultural differences, managers will be able to manage their business more effectively. Additionally, appropriate motivation strategies can be adopted to suit the various ethnic groups' motivation needs. Lastly, business managers in Singapore are advised to place more emphasis on human resource training. Ultimately, a well-trained workforce will be an competitive advantage for Singapore.